El liderazgo y su relación con la satisfacción de los clientes: un enfoque teórico - Villanueva Sampín, Stefanie Desiré (2018)
In every organizationit is important that each group has an established structure, where there will always be those who assume a greater degree of responsibility, evaluate, make decisions and have their approach based on organizational objectives. Therefore, it is very natural that in any work group a leader stands out, which contributes to the development and achievement of the established objectives.There are several types of leadership, but whatever the profile of the same, the main objective should be aimed at leading the group towards success and in the business, environment is not an exception. For the client to perceive a good service and be sati sfied with it, the employee must feel motivated, that is why the importance of the figure of the leader.